16‐2: Remarkable Improvement of Electro‐Mechanical Stabilities in Flexible Oxide TFTs under Bulk‐Accumulation Operation. Issue 1 (29th May 2019) - Billah, Mohammad Masum; Jang, Jin
Abstract : We demonstrate highly‐robust flexible dual‐gate (DG) a‐IGZO TFTs on polyimide (PI) substrate. DG‐driving TFTs exhibit robust mechanical stability as compared to SG‐driving, which might be originated from the strain‐limiting top‐gate (TG) that efficiently modulates neutral‐plane (NP). TCAD simulation confirms the improved stability of DG‐TFTs due to smaller strain and increased electron concentration in a‐IGZO channel than SG‐driving TFTs.